Implementation of a cascade training model to enhance emergency care capacity of healthcare workers during the COVID-19 outbreak in Uganda - Wasukira, Sulaiman Bugosera; Kambugu, Carl Trevor; Ikwaru, Patricia; Murungi , Costance; Alenyo-Ngabirano, Annet (African Journal of Emergency Medicine, 2025)
The COVID-19 pandemic highlighted the gaps and the need to strengthen the emergency care system in Uganda. The Ugandan Ministry of Health implemented an emergency care capacity-building program during the COVID-19 pandemic response to improve COVID-19 case management in Uganda. We describe the curriculum development and rollout using a cascade model.